Social Media Marketing: Engaging with Consumers in Digital Era - Aleksandar Grubor; Olja Jakša (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
In technology driven world, social media has become one of the cornerstones for growing a successful business. As a costly-effective tool, it overcomes traditional media channels, improves word-of-mouth communication and transforms business models adjusting them to the next generation of interaction with whole market in digital environment. Various social media platforms provide wide spectrum of options for creative approach in engaging consumers, taking them and their whole network of connections on an exciting decision journey, through each step of marketing funnel. Embracing inputs from all users, social media marketing is evolving each day and generates numerous opportunities for digital marketing managers. Consequently, it has become top communication priority, which is both challenging and risky, but inevitable part of integrated marketing communication strategy. Thus, the aim of this paper is to point out all dimensions of social media marketing in digital era, by analysing theoretical and practical standpoints from the available literature, scientific papers and studies in the given field.
Keywords: M31; 330; social media marketing; digital marketing; internet marketing; online marketing